2005
DOI: 10.4315/0362-028x-68.4.850
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Yersinia enterocolitica in Fattening Pigs

Abstract: The prevalence of pathogenic Yersinia enterocolitica in pig herds was monitored during six trials (at four different farrow-to-finisher farms). Samples were taken throughout the whole rearing period from birth of the piglets to the final fattening stage, and different samples were taken from these pigs during the slaughter process. Environmental samples also were evaluated to identify potential sources of on-farm infection. Y. enterocolitica was isolated using irgasan-ticarcillin-potassium chlorate broth enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
61
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 23 publications
(25 reference statements)
10
61
1
1
Order By: Relevance
“…In contrast, only the tonsils were efficiently colonized by O:8 in some of the infected minipigs. These results are in agreement with previous observations in surveys that reported that mainly serotype O:3 strains were isolated from the oral cavity, intestinal tract, and feces of pigs (21,38,39). Young pigs generally get infected within the first 3 weeks after entering contaminated areas (e.g., pens) or by other infected pigs, and they remain intestinal and pharyngeal carriers for long time periods (38).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, only the tonsils were efficiently colonized by O:8 in some of the infected minipigs. These results are in agreement with previous observations in surveys that reported that mainly serotype O:3 strains were isolated from the oral cavity, intestinal tract, and feces of pigs (21,38,39). Young pigs generally get infected within the first 3 weeks after entering contaminated areas (e.g., pens) or by other infected pigs, and they remain intestinal and pharyngeal carriers for long time periods (38).…”
Section: Discussionsupporting
confidence: 83%
“…An increase in the prevalence in feces up until 16 weeks of age of the pigs was noted, which was followed by a decrease over time until the end of the follow-up. This pattern is in agreement with previous studies (11,14,25). Despite the low fecal prevalence at the end of the period, most of the sampled pigs were seropositive at the time of slaughter.…”
supporting
confidence: 82%
“…In the study of Nesbakken et al (2003), the proportion of pathogenic Yersiniae detected in tonsils compared to faeces was six to one. These proportions are similar to findings by Frederiksson-Ahomaa et al (2007) and Gürtler et al (2005), who reported that the frequency of isolated pathogenic Yersiniae was significantly greater from tonsils than that obtained from faeces at slaughter. In conclusion, when the pigs are slaughtered at the age of 135 days or more, the tonsils are a more significant source of human pathogenic Y. enterocolitica than faeces (Nesbakken et al, 2006).…”
Section: The Rationale Behind the Choice Of Culture From Tonsilssupporting
confidence: 91%